Evaluation of helium ions energy loss within material of vacuum chamber inner walls of the AECS-PF1 device (Journal of Al-Wataniya Private University, 2025)
In this research, helium ions energy loss emitted by AECS-PF1 dense plasma focus device was evaluated through their collision with electrodes and inner walls of vacuum chamber. First, plasma focus parameters and ion beams characteristics when the pressure of helium gas changes were determined using Lee's code. The ions energy loss was found in tungsten, stainless steel and copper. The results showed a high energy loss in tungsten compared to stainless steel and copper due to the high number of electrons, as the ions lose most of their energy through elastic collision with the electron cloud, thus causing cracks and bulges in the surface layer of Tungsten is larger than stainless steel and copper